Governance Through Ownership: Centuries of Practice, Decades of Research - Daily, Catherine M.; Dalton, Dan R.; Rajagopalan, Nandini (Academy of Management Journal, 2003)
The governance of organizations with dispersed ownership has received academic attention for over seven decades. Early research focused largely on managerial opportunism and mechanisms for minimizing its impact on shareholder wealth. The governance landscape has dramatically changed in the past several decades with the emergence of powerful owners such as institutional investors and large blockholders, as well as increased reliance on equity-based forms of compensation. Contemporary researchers must account for the impact of these diverse owners on organizations' governance and performance. This Special Research Forum on Governance through Ownership is dedicated to furthering this rich tradition of research.